Organic semiconductors for biocompatible and transient electronic devices - Li, Ting (Nanyang Technological University, 2024)
Organic electrochemical transistors (OECTs) can efficiently convert ionic signals into electronic signals and exhibit high transconductance, fast response, and low operating voltage, making them ideal for biomedical applications such as physiological signal detection. However, preparing OECTs and using them in practical applications requires addressing a number of issues. First, the organic semiconductor used as the OECT channel should have good mixed ionic and electronic transport capability, which is the key to preparing high-performance OECTs. In addition, excellent biocompatibility will be necessary for on-skin electronic devices. To reduce the burden of electronic waste on the environment, it is also important to develop devices with transient functionality and recyclability. Many reported methods for preparing high-performance OECTs involve the use of toxic and hazardous additives and agents that are inappropriate for preparing on-skin devices due to the scarcity of biocompatibility. In this thesis, we suggest the use of green chemicals to prepare poly(3,4-ethylenedioxythiophene):poly(styrene sulfonate) (PEDOT:PSS)-based OECTs. The resultant OECTs show higher transconductance, faster transient response, and excellent stability. We also develop OECTs with transient functionality as ways to demonstrate the practicality of reducing the burden stemming from electronic waste on the environment. In this thesis, two different methods are proposed for preparing transient organic semiconductors. The hybrid electronic and ionic transport property of the resultant transient organic semiconductors are investigated in detail, thus facilitating the development of high-performance transient OECTs. Moreover, high-performance inverters are enabled and electrocardiogram signals are well-captured by these transient OECTs. Furthermore, these transient OECTs demonstrate good transient functionality and controllable device failure, showing the potential for high-performance transient electronic devices.